Beyond Self-Translation and Translation in Licia Canton’s The Pink House and Other Stories - Spadafora, Maria Pia (Italian Canadiana, 2023)
Despite the vast field represented by translation and self-translation, there is much more to say about these two distinctive practices and their differences within the Canadian landscape. This paper focuses on Licia Canton’s short-story collection The Pink House and Other Stories. It discusses the self-translated stories in the collection, comparing them with other stories which I have attempted to translate into Italian. By referring to the work of scholars such as Popovîc, Grutman, Blanco, Tanqueiro, Serafin, Bassnett, Tagore, and Gumperz, this paper aims to highlight what is inevitably lost in translation whilst underlining the importance of self-translation in the Canadian context.